Commitment, partnerships and operational research: three priorities for 11 EMR countries to achieve TB elimination - M. van den Boom; K. Bennani; G. B. Migliori; L. D’Ambrosio; R. Centis; A. Parvez Sayed; H. Y. Atta; Y. Hutin (IJTLD Open)
BACKGROUND: In 2022, 11 of 22 Member States of the WHO Eastern Mediterranean Region (EMR) had an estimated TB incidence of <20 cases per 100,000 population. We assessed preparedness for elimination and provided recommendations to pursue the process. METHODS: We surveyed 11 EMR national TB programme managers and collected information on eight TB elimination framework domains using a close-ended data collection tool. We compiled, consolidated and validated data, including a virtual consultation before triangulating data with other sources. RESULTS: Implementation was sufficient (≥74%) for 5 of 8 domains, highest for TB infection management, TB preventive treatment, laboratory service, drug management, drug-resistant TB and TB-HIV collaboration (89%, 83% and 78%, respectively). Countries ranked lowest for commitment (73%), operational research and infection control (63%), and partnership/collaborations (41%). Five countries reached >80% when consolidating the responses, reaching sufficient from all domains. Two reached <50%. CONCLUSION: Key identified obstacles to TB elimination in EMR were insufficient commitment/financing, sub-optimal partnerships/collaborations and operational research calling for 1) all-stakeholder-inclusive, sustainably funded TB elimination plans, 2) cost-effective tools to exchange strategic information and build operational research capacity, and 3) improved collaboration.